Analytical solutions of a certain class of integral equations - Miroliubov, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Миролюбов. Аналитические решения одного класса интегральных уравненийA. Miroliubovas. Vienos klasės integralinių lygčių analiziniai sprendiniai